Biocontrol Ability and Action Mechanism of Starmerella bacillaris (Synonym Candida zemplinina) Isolated from Wine Musts against Gray Mold Disease Agent Botrytis cinerea on Grape and Their Effects on Alcoholic Fermentation - Lemos Junior, Wilson José Fernandes; Bovo, Barbara; Nadai, Chiara; Crosato, Giulia; Carlot, Milena; Favaron, Francesco; Giacomini, Alessio; Corich, Viviana (Frontiers in Microbiology, 2016)
Gray mold is one of the most important diseases of grapevine in temperate climates. This plant pathogen affects plant growth and reduces wine quality. The use of yeasts as biocontrol agents to apply in the vineyard have been investigated in recent years as an alternative to agrochemicals. In this work, fermenting musts obtained from overripe grape berries, therefore more susceptible to infection by fungal pathogens such as Botrytis cinerea, were considered for the selection of yeasts carrying antifungal activity. Thirty-six isolates were identified as Starmerella bacillaris, a species recently proven to be of enological interest. Among them 14 different strains were studied and antifungal activity against B. cinerea was demonstrated, for the first time, to be present in S. bacillaris species. The production of volatile organic compounds (VOCs), tested in vitro, was found to be the main responsible of S. bacillaris antifungal effects. All the strains were able to reduce B. cinerea decay on wounded grape berries artificially inoculated with gray mold. The colonization level of wound was very high reaching, after five days, a concentration of 106 cells per ml of grape juice obtained after berry crushing. At this cell concentration S. bacillaris strains were used to ferment synthetic and natural musts. The sequential yeast inoculation, performed by adding S. cerevisiae 48 h after S. bacillaris, was needed to complete sugar consumption and determined a significant increase in glycerol content and a reduction of ethanol and acetic acid concentrations. The high wound colonization ability, found in this work, together with the propensity to colonize grape berry and the interesting enological traits possessed by the selected S. bacillaris strains allow the use of this yeast as biocontrol agent on vine and grape berries with possible positive effects on must fermentation, although the presence of S. cerevisiae is needed to complete the fermentation process. This work introduces new possibilities in wine yeast selection programs in order to identify innovative wine yeasts that are simultaneously antifungal agents in vineyards and alternative wine starters for grape must fermentation and open new perspective to a more integrated strategy for increasing wine quality.